The Use of Socioscientific Issues in Science Learning: Review Literature - Nurul Hidayah Nasution; Irda Wahidah Nasution (International Journal Of Humanities Education and Social Sciences (IJHESS), 2026)
The goal of education is to develop students' abilities. These abilities are expected to grow and develop in accordance with the values ​​prevailing in society and the nation's culture. The approach related to scientific and social issues is known as the socioscientific approach. In general, this approach provides a way for students to learn about scientific research through case development, which can be implemented through classroom discussions and problem-based learning. The method applied in this article is the  review literature Study (SLR). This approach is generally used to review articles and publish the results of the review in new articles. The procedures used in this technique include formulating the topic to be researched, establishing inclusion and exclusion criteria or a screening process. If necessary, these elements are found and then analyzed. The results of the analysis are organized based on what has been read. Articles to be analyzed will be obtained by searching the Publish Or Perish application for databases from Google Scholar and Crossref, searching for research literature that aligns with the keywords: socioscientific issues in science learning. The SLR method allows researchers to systematically review and identify journals where each process follows predetermined steps. The inclusion criteria used were articles from 2023-2026, research topics covering socioscientific issues in science learning. Exclusion criteria were research articles that cannot be accessed completely, are not full text, non-science, non-junior high school, and all those in languages ​​other than English and Indonesian. The literature stages are based on using Research Questions to make the discussion more focused and to make it easier for researchers in the review literature process. Socioscientific issues (Socioscientific Issues) are issues that describe social problems in society within a conceptual, procedural, or technological context of science. The use of socioscientific issues in science learning can encourage students to actively engage in dialogue, discussion, and debate, which can provide opportunities for them to evaluate their understanding and improve their mastery of concepts related to the material they have learned. Currently, one of the topics being discussed is environmental challenges, namely climate change and rising global temperatures. Global temperature rise is a phenomenon that can be studied and addressed with the help of science.